Effects of different polishing techniques on the surface roughness of dental porcelains - Işil Sarikaya; Ahmet Umut Güler (University of São Paulo, 2010)
OBJECTIVE: The purpose of this study was to evaluate the effects of different polishing techniques on the surface roughness of dental porcelains. MATERIAL AND METHODS: Fifty-five cylindirical specimens (15x2 mm) were prepared for each feldspathic (Vita VMK 95, Ceramco III) and low-fusing dental porcelain (Matchmaker). Fifty-five specimens of machinable feldspathic porcelain blocks (Vitablocs Mark II), (12x14x18 mm) were cut into 2-mm-thick slices (12x14 mm) with low speed saw. The prepared specimens were divided into 11 groups (n=5) representing different polishing techniques including control ((C) no surface treatment), glaze (G) and other 9 groups that were finished and polished with polishing discs (Sof-Lex) (Sl), two porcelain polishing kits (NTI (Pk), Dialite II (Di)), a diamond polishing paste (Sparkle) (Sp), a zirconium silicate based cleaning and polishing prophy paste (Zircate) (Zr), an aluminum oxide polishing paste (Prisma Gloss) (Pg), and combinations of them. The surface roughness of all groups was measured with a profilometer. The data were analyzed with a 2-way analysis of variance, and the mean values were compared by the Tukey Honestly Significant Difference test (a=0.05). RESULTS: For all porcelain material groups, the lowest Ra values were observed in Group Gl, Group Sl, Group Pk, and Group Di, which were not significantly different from each other (p>0.05).When comparing the 4 different porcelain materials, the machinable feldspathic porcelain block group (Mark II) demonstrated statistically significantly less Ra values than the other porcelain materials tested (p<0.05). No significant difference was observed between the VMK 95 and Ceramco III porcelain groups (p=0.919), also these groups demonstrated the highest Ra values. CONCLUSION: Subjected to surface roughness, the surfaces obtained with polishing and/or cleaning-prophy paste materials used alone were rougher compared to the surfaces finished using Sof-lex, Dialite, and NTI polishing kit. Polishing kits and discs were found more effective than the polishing pastes used alone or combined use with Sof-lex discs, thus improving surface smoothness.